Orthodontic Extrusion with Circumferential Supracrestal Fiberotomy: A Report of Two Cases - (:unkn) unknown (AVES, 2018)
Surgical extrusion, surgical crown lengthening, and orthodontic extrusion (OE) with circumferential supracrestal fiberotomy (CSF) are reported as effective methods in cases when clinical crowns are destroyed. The aim of these case reports was to evaluate the results of OE+CSF in a canine and a mandibular second molar tooth. Case 1: A 24-year-old male patient was referred with a fracture of the maxillary canine at the subgingival level. After the examinations, OE+CSF was planned. Following leveling-aligning, a mini-screw was placed into the root canal of the canine, and 50 g of extrusive force was applied from the mini-screw to a stainless steel (SS) wire. Case 2: A 67-year-old female patient was referred with a mandibular second molar destroyed at the gingival level. OE+CSF was planned. An extrusive force (50 g) was applied from the segmental SS wire to the hook inserted into the root canal. CSF and root planning (RP) were performed weekly in both patients. Overall, 5 mm of extrusion was achieved for the upper canine after 6 weeks of active extrusion in Case 1. In Case 2, 5 mm of extrusion was achieved after 3 weeks of active extrusion. OE+CSF is an effective and rapid method for the extrusion of teeth with insufficient clinical crown.
Keywords: Circumferential supracrestal fiberotomy; orthodontic extrusion; FORCED ERUPTION; CROWN